A multiple-vehicle strategy for near-Earth asteroid capture. (October 2022) - Ionescu, Livia; McInnes, Colin R.; Ceriotti, Matteo
Abstract: The use of asteroid resources could benefit future space missions. Instead of lifting the necessary materials off the Earth, they can be then sourced directly in space. Asteroid capture missions aim to bring asteroids closer to Earth, where they can be permanently accessed. This paper introduces a new strategy for asteroid capture missions, where two spacecraft are used for capturing near-Earth asteroids. These spacecraft act together as a 'pitcher' spacecraft and 'catcher' spacecraft, where the pitcher spacecraft hops from asteroid to asteroid and deflects them towards an orbit in the vicinity of Earth, while the catcher spacecraft is stationed at the Earth and captures the incoming asteroids. This novel two-spacecraft strategy is compared to a conventional one-spacecraft strategy using three analyses; a preliminary analysis using coplanar and circular orbits to define the problem, a statistical analysis using fictional near-Earth asteroids to obtain a large set of data, and an analysis where real near-Earth asteroids are used as mission targets. A mass model is developed to compute the retrieved asteroid mass per unit of initial wet spacecraft mass for missions aiming to retrieve multiple asteroids. Results show that the two-spacecraft strategy is capable of returning more asteroid mass and often at a shorter mission duration. Highlights: A multiple-vehicle strategy is developed for the capture of near-Earth asteroids. The retrieved asteroid mass ratio is compared against using a single spacecraft. The multiple-vehicle strategy can return more mass in a shorter mission time.